Agroforestry potential for adaptation to climate change: A soil‐based perspective - Rolo, Víctor; Rivest, David; Maillard, Émilie; Moreno, Gerardo (Soil use and management, 2023)
Agricultural systems face several challenges that threaten their capacity to feed the world while maintaining a healthy and functional environment. Climate change, together with soil degradation, biodiversity loss, resource scarcity and invasive species, is a major threat to agricultural systems worldwide. In this context, new practices have been proposed to circumvent or minimize these threats. Yet, these mostly focus on the farm or plant level (e.g., breeding for stress‐tolerant species), while frequently overlooking belowground components (e.g., soil organic carbon accrual). By interlinking above‐ and below‐ground components, the likelihood of limiting the negative effects of current threats to agricultural systems can be maximized. This review explores current knowledge regarding agroforestry and its effects on belowground components as a key property in the reducing effects of climate change. We first review tree effects on key soil properties of agricultural systems. We synthesize evidence regarding agroforestry systems response to current environmental threats that are related to climate change. We continue by discussing how soil processes play a fundamental role in the capacity of agroforestry systems to cope with climate change. We conclude by proposing options on how resilience of agroforestry systems could be further enhanced.